#TITLE_ALTERNATIVE# - NURROSYID P (NIM: 10511092), NAUFAN
The potential of thiazole derivative molecule has analyzed as an active molecule in the dye sensitized solar cell because of itÃ‚Â’s D-π-A structure. The calculations were performed by ab-initio computation using the High Performance Computing (HPC)-ITB with Gaussian 09 software, DFT approach (ground state) and TDDFT (excitation state). Both of them used B3LYP function with 6-31G (D) for ground state and cc-PVDZ for excitation. All of calculations were stimulated in ethanol solvent. Result of calculations obtained two point, there are number of thiophene variation (1, 2, 3, 10) and fuction group addition ( Ã‚Â–H, -NH2, -OCH3 and -COOH ) for variation of electron donating group. Parameter of analysis was performed by calculations of optimated structure, excitation energy, composition and symmetry excitation, density of the molecular orbitals, and UV-Vis absorption spectra. Geometry optimized calculations showed the planar shape for all variety. Excitation energy in number of thiopene group which has been modeled, showed low values by addition of the group. The best result was 10 thiophenes which have excitation symmetry in HOMO  LUMO and had 91% for the excitation composition. UV-Vis absorption from these variants showed absorption peak at 667.54 nm and osilator strenght (fosilator) 4.24. While the best calculation result of variations in the electron donor group showed by addition of the amine group, excitation energy was 1,96 eV, single symmetry HOMO  LUMO, and the excitation composition reaches 100%. UV-Vis absorptions of this variant also indicated the absorption peak at 632.57 nm and fosilator 1.05. Distribution of HOMO-LUMO in all variants showed that the thiazole derivative can be excited qualitatively. Beside of that, trans geometry with 10 thiophene group was performed by addition of -NH2 as electron donating groups, the excitation energy 1,66 eV, three dominant excitation symmetry in HOMO  LUMO, and 79% for the excitation composition. This model had a best molecular orbitals density with UV-Vis UV-Vis absorption at a red light wavelength, 673.20 nm and fosilator 2.29.